Pelatihan Pembuatan Hand Sanitizer dari Bahan-Bahan Organik Sebagai Tindakan Pencegahan Penyebaran Penyakit di Dusun Berembeng Desa Jurang Jaler - Pahrur Rozi; Dwi Agustin; Leny Fitriah; Baiq Naily Dewi Atika (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2021)
Abstact Coronavirus-19 has become a global pandemic except in Indonesia. This virus causes us to apply health protocol. One of these is regularly to wash our hands with soap. Our hands become medium to spear up bacteria and viruses because we use to touche other human and things. The other alternative besides washes our hands is using hand sanitizer to constitute a material to wash our hands without water. Hand sanitizer normally produces with a chemical ingredients, wich harms the skin for long application. The exist of hand sanitizer with the natural ingredients has to reduce harms to the skin, but effectively controlling bacteria and viruses. This training aims to share knowledge and procedur to make a hand sanitizer with natural ingredients such as Averrhoa bilimbi, Aloe vera, Mint, and Citronella. These ingredients contain natural antiseptic such a flafonoid, saponin, and tannin.